Cryopreservation of Human Fetal Fibroblast Culture - Timon, V. V.; Petrenko, T. F.; Goncharuk, E. I. (Problems of Cryobiology and Cryomedicine, 2007)
Cryoprotective properties of 1,2-propanediol (1,2-PD), oxyethylated glycerol (OEG; n=5) and fetal calf serum (FCS) when freeze-thaw human fetal fibroblast (HFF) culture were studied. It has been established that 1,2-PD and OEG have weak cryoprotective properties and do not provide the integrity of functional activity of HEF cells. Cell cryopreservation in FCS provided maximum integrity of cells and their functional activity.